Pengaruh Managerial Coaching dan Team Autonomy terhadap Kinerja Karyawan di Perusahaan Perkebunan dan Pengolahan Kelapa Sawit di Pulau Sumatera - Fajar Rezeki Ananda Lubis; Syaifuddin Syaifuddin; Yusniar Lubis; Nasib Nasib (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2023)
This study aims to examine the influence of managerial coaching and team autonomy on employee performance and to evaluate the mediating role of work climate on the influence of managerial coaching and team autonomy on work engagement. Additionally, this study investigates the role of work engagement as a mediator between managerial coaching, team autonomy, and work climate on employee performance in palm oil plantations and processing companies in Sumatra. The sample consists of 523 employees. Structural Equation Modeling Partial Least Squares (SEM PLS) is the analysis method. The results indicate that managerial coaching significantly influences work climate and work engagement, and team autonomy also significantly influences work climate and engagement. Work climate significantly influences work engagement and employee performance, and work engagement significantly influences performance. The indirect effects analysis shows that work climate mediates the influence of team autonomy on work engagement, and work engagement mediates the influence of managerial coaching and team autonomy on performance.